A study on relationship between quality of life and employee performance - Marziyeh Pourbagher; Ali Akbar Bani; Mehdi Salehi; Somayyeh Iri; Saeid Sedaghat (Management Science Letters)
This paper studies the relationship between quality of life and its eight components with employee performance in general directorate of youth and sport in province of Golestan, Iran. The study uses a questionnaire developed by Walton (1974) [Walton, R. E. (1974). Improving quality of work life. Harvard Business Review, 52(3), 12.] for quality of life and a standard questionnaire named ACHIEVE consists of 25 questions for measuring the performance. Using Spearman correlation test, the study has determined a positive and meaningful relationship between employee performance and eight components of Walton’s model including adequate and fair compensation, safe and healthy working conditions, development of human competencies, growth and security, social integration, constitutionalization and total life space and social reliance.